2014
DOI: 10.5897/ajar12.2174
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the operations and challenges of pig butchers in rural and peri-urban settings of western Kenya

Abstract: The purpose of this cross-sectional, observational study was to describe the pig butcher enterprises in western Kenya; highlighting differences in the operational processes and challenges between rural and peri-urban settings. Fifty pig butchers were interviewed using questionnaires in two districts, Kakamega (peri-urban) and Busia (rural). Results showed that pig butchers were central to the coordination of activities required to connect pig farmers to pork consumers in their communities. Several differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…These findings are similar to others who report the ability of smallholder farming widows in western Kenya to do "everything [related to the pig enterprise] all by herself " [30]. Moreover, other researchers report that in western Kenya, 46% females and 54% males negotiated the selling price with butchers indicating men and women are both involved in pig sales in east Africa [60].…”
Section: Deception and Evasionsupporting
confidence: 77%
“…These findings are similar to others who report the ability of smallholder farming widows in western Kenya to do "everything [related to the pig enterprise] all by herself " [30]. Moreover, other researchers report that in western Kenya, 46% females and 54% males negotiated the selling price with butchers indicating men and women are both involved in pig sales in east Africa [60].…”
Section: Deception and Evasionsupporting
confidence: 77%
“…The main marketing channel was from producer-trader-supermarket-hotel/restaurant-consumer. In agreement with the current study, In Western Kenya, pigs are not sold in a central market; instead, butchers purchased pigs directly from the smallholder farmer at the farm gate (Levy et al, 2014). Unlike to Ethiopian, live pigs are sold at local village markets to intermediate traders in Nigeria (Ajala and Adesehinwa, 2008).…”
Section: Source Of Pork Supplysupporting
confidence: 74%
“…In North western Ethiopia, pigs are sold for external markets as pork is not consumed by local community (Mekuriaw & Asmare, 2014). In western areas of Kenya pork is sold in local shops either as raw pork or as cooked pork where most of butchers (59%) sold raw pork but 41% of them sold cooked pork (Levy et al, 2014). This study found that pork marketing was less competent as compared to beef marketing ( Figure 1).…”
Section: Pork Vs Other Meat Types Marketingmentioning
confidence: 87%
See 1 more Smart Citation
“…Importantly, we also find that the distances that free range pigs move on a daily basis (mean of 4.1 km during daylight and 4.5 km at night) are likely to entail high energy expenditure. Mature pigs 6–10 months old presenting at slaughter in this region have been found to have mean live weights at the abattoir of 30 kg, giving a dressed weight of only 22.5 kg and earning the farmer only 2,000–2,500 KES [60], equivalent to US$24–29 per animal. Encouraging the confinement of pigs is likely to improve feed conversion and weight gain, by both reducing un-necessary energy expenditure as well as limiting parasite burden through environmental exposure.…”
Section: Discussionmentioning
confidence: 99%